Evidence From the Decade of Action for Road Safety: A Systematic Review of the Effectiveness of Interventions in Low and Middle-Income Countries - Maryam Tavakkoli; Maryam Tavakkoli; Zahra Torkashvand-Khah; Günther Fink; Günther Fink; Amirhossein Takian; Nino Kuenzli; Nino Kuenzli; Don de Savigny; Don de Savigny; Daniel Cobos Muñoz; Daniel Cobos Muñoz (Frontiers Media S.A., 2022)
Objectives: To evaluate the effectiveness of road safety interventions in low and middle-income countries (LMICs), considering the principles of systems theory presented in the Global Plan for the Decade of Action for Road Safety.Methods: We conducted a systematic review according to PRISMA guidelines. We searched for original research studies published during 2011-2019 in the following databases: Medline, Embase, PsycInfo, Scopus, Web of Science, Cochrane library, Global Health Library, ProQuest and TRID. We included studies conducted in LMICs, evaluating the effects of road traffic safety interventions and reporting health-related outcomes.Results: Of 12,353 non-duplicate records, we included a total of 33 studies. Most interventions were related to legislation and enforcement (n = 18), leadership (n = 5) and speed management (n = 4). Overall, legislation and enforcement interventions appear to have the largest impact. Few studies were found for road infrastructure, vehicle safety standard and post crash response interventions.Conclusion: Based on the currently available evidence, legislation and enforcement interventions appear most impactful in LMICs. However, many interventions remain understudied and more holistic approaches capturing the complexity of road transport systems seem desirable.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=197267, identifier CRD42020197267.